Engineering Atomically Dispersed FeN4 Active Sites for CO2 Electroreduction. (12th November 2020) - Mohd Adli, Nadia; Shan, Weitao; Hwang, Sooyeon; Samarakoon, Widitha; Karakalos, Stavros; Li, Yi; Cullen, David A.; Su, Dong; Feng, Zhenxing; Wang, Guofeng; Wu, Gang
Abstract: Atomically dispersed FeN4 active sites have exhibited exceptional catalytic activity and selectivity for the electrochemical CO2 reduction reaction (CO2RR) to CO. However, the understanding behind the intrinsic and morphological factors contributing to the catalytic properties of FeN4 sites is still lacking. By using a Fe‐N‐C model catalyst derived from the ZIF‐8, we deconvoluted three key morphological and structural elements of FeN4 sites, including particle sizes of catalysts, Fe content, and Fe−N bond structures. Their respective impacts on the CO2RR were comprehensively elucidated. Engineering the particle size and Fe doping is critical to control extrinsic morphological factors of FeN4 sites for optimal porosity, electrochemically active surface areas, and the graphitization of the carbon support. In contrast, the intrinsic activity of FeN4 sites was only tunable by varying thermal activation temperatures during the formation of FeN4 sites, which impacted the length of the Fe−N bonds and the local strains. The structural evolution of Fe−N bonds was examined at the atomic level. First‐principles calculations further elucidated the origin of intrinsic activity improvement associated with the optimal local strain of the Fe−N bond. Abstract : We comprehensively engineered atomically dispersed and nitrogen‐coordinated FeN4 sites for electrochemical CO2 reduction to CO considering the particle sizes of the catalysts, Fe content, and the Fe−N bond structures. The unique Fe‐N‐C model allows us to elucidate each factor′s role exclusively regarding the promotion of CO2 reduction. Optimal particle sizes and Fe content provide favorable external factors to improve mass activity. Structural changes of Fe−N bonds controlled by thermal activation temperatures can intrinsically enhance both the CO selectivity and kinetic activity.